The effect of morpheme positional frequency on tibetan novel word acquisition: An eye-tracking study - Dingyi Niu; Jing Tian (PLoS ONE, 2025)
Word segmentation is crucial for reading in unspaced languages like Tibetan, where readers rely on high-level cues like morpheme positional frequency (the statistical likelihood of a morpheme appearing at the beginning or end of a word). Using a novel word learning paradigm, this study investigated whether initial and final morpheme positional frequency facilitate word segmentation and lexical recognition in Tibetan. In two eye-tracking experiments, participants read sentences containing novel words manipulated for initial (Experiment 1) or final (Experiment 2) morpheme positional frequency across learning and testing phases. Results showed that while initial morpheme positional frequency influenced saccade target selection and the late stage of lexical recognition, final morpheme positional frequency primarily affected late stage of lexical recognition. Reading phase improved efficiency across all measures. The effects of morpheme positional frequency and the reading phase were independent at both early and late stages of lexical recognition. Findings provided evidence that morpheme positional frequency may serve as a functional word segmentation cue in the context of Tibetan novel word acquisition.